The application of methacrylate resin and the derivation as restorative material of damaged tooth tissue - Adioro Soetojo (Dental Journal (Majalah Kedokteran Gigi), 2007)
The application of methacrylate resin and the derivation (composite resin and dentin bonding) in clinical conservative dentistry has been widely developed. This material could be used to restore class I-V cavity with good aesthetic due to the compatible color with tooth. Composite resin adhesion hydrophobically in enamel that is due to mechanic retention in the form of resin tags which penetrates into enamel porosity. Meanwhile hydrophilic dentin bonding adhesion due to the chemical reaction between functional groups of amino collagen with carbonyl in dentin bonding forming amide binding. In addition mechanical retention in which dentin bonding penetrating into nano inter fibrilar cavity then polymerized. The success of methacrylate resin adhesion restoration is decided by enamel porosity, wetting character of resin, wetting contact angle, good etching acid, optimal humidity of tooth surface, the accuracy of dentist during filling is done etc.